The effect of UV radiation, cooking and storage on the D vitamer content of dried Agaricus bisporus mushrooms - Cardwell, Glenn (Curtin University, 2023)
Fresh button mushrooms exposed to pulsed UV radiation, then air-dried, increase their D vitamer concentration to a level of human nutritional importance. About two thirds of the D vitamers are retained after 12 months of storage. Furthermore, virtually all the D vitamers are retained after common household cooking methods. UV-irradiated dried mushrooms are a long shelf-life, convenient source of D vitamers with the potential to reverse or prevent vitamin D deficiency.